Histological Characteristics of Conjunctiva-Associated Lymphoid Tissue in Young and Adult Holstein Cattle - Keigo Kosenda; Osamu Ichii; Yusuke Yamashita; Hiromichi Ohtsuka; Shigeo Fukuda; Yasuhiro Kon (Animals, 2023)
The conjunctiva-associated lymphoid tissue (CALT) has been used as a target site for mucosal vaccinations in several animals. In this study, we compared the morphological features of CALT in the eyelid and third eyelid between Holstein calves and adult cows. In the eyelids, CALTs in the form of diffused lymphoid tissue (DLT) and lymphatic follicles (LF) were observed, where DLTs were dominant and LFs were scarce. The CALTs of cows comprised T-, B-cells, macrophages, and antigen-presenting cells (APCs). In particular, B-cells were dominant except in the eyelids of the calves. The epithelial layer covering the CALT is often discontinuous and lacks goblet cells. Cytokeratin18 is strongly expressed in the epithelial layer covering the CALT, except in the third eyelids of adult cows. IgA-positive cells were diffusely distributed in the lamina propria of the conjunctiva of the eyelids and third eyelids. The eyelid CALT area in calves was lower than that in adult cows. Furthermore, the CALT of calves had a lower cellularity of B-cells and a higher cellularity of macrophages than that of adult cows. These histological characteristics indicate that CALT plays a role in the mucosal immune-inductive and effector sites. Furthermore, lower cellularity of B-cells in the CALT of calves indicates that the function of CALT as a mucosal immune induction site is less developed in calves than in adult cows.